Sociolegal social work in the field of criminal defense - Norambuena-Conejeros, Felipe (Latin American social work in the justice system, 2023)
This chapter deals with the professional work of the sociolegal social worker in the context of the Chilean criminal justice system. It is carried out through an investigation to social workers who work in different units of the public criminal defender, contrasting the above with a bibliographic review of the main topics of interest for the area and the work that is developed there, emphasizing the social contexts of intervention and the professional challenges of those who work in this field of professional development.